2019
DOI: 10.21203/rs.2.16283/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Psychological resilience and health-related quality of life in Swedish women with newly diagnosed breast cancer

Abstract: Purpose Psychological resilience appears to be an important influencing factor in various aspects of health-related quality of life (HRQoL) in a context of adversity, e.g., being informed of a cancer diagnosis. The purpose was to investigate psychological resilience and health-related quality of life in Swedish women with newly diagnosed breast cancer in relation to demographic and clinicopathological characteristics.Methods A population-based cross-sectional study was conducted including 517 women with breast… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 20 publications
3
4
0
1
Order By: Relevance
“…This reflects the fact that positive psychological states can be shown in different aspects, and are positively correlated with each other [23]. Consistent with previous reports, it was found that confrontation, perceived social support, and resilience were positively associated with HRQoL, which indicated that a sound psychological state was beneficial to HRQoL improvement [8][9][10][11][12]. Although avoidance is a negative coping style, it was still helpful in protecting the BCSs' psychological defense system, which allowed more time for them to recover from their distress [24].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This reflects the fact that positive psychological states can be shown in different aspects, and are positively correlated with each other [23]. Consistent with previous reports, it was found that confrontation, perceived social support, and resilience were positively associated with HRQoL, which indicated that a sound psychological state was beneficial to HRQoL improvement [8][9][10][11][12]. Although avoidance is a negative coping style, it was still helpful in protecting the BCSs' psychological defense system, which allowed more time for them to recover from their distress [24].…”
Section: Discussionsupporting
confidence: 88%
“…Apart from the above-mentioned variables reported by systematic reviews, resilience and perceived social support are also factors related to HRQoL [11,12], along with higher resilience and perceived social support were associated with better HRQoL [11,13]. Resilience is regarded as the most important factor that should be assessed at the time of breast cancer diagnosis, which allows early identification of patients who may need more psychological support [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polikandrioti et al also found that the decrease of social support was significantly related to the increase of depression in DFU patients and the presence of depression would further affect the QoL of patients (18). Most importantly, low psychological resilience was identified as an important risk factor of QoL in DFU participants in our study, which is similar to how it has been shown to influence patients with other diseases (13,14).…”
Section: Discussionsupporting
confidence: 83%
“…Psychological resilience refers to how people react psychologically and behaviorally to change in their external environment. It has been reported that improved psychological resilience was related to higher QoL in patients with inflammatory bowel disease, breast cancer, and hypertension (13)(14)(15). However, no related study has yet been performed to investigate the impacts of psychological resilience on QoL in DFU patients.…”
Section: Introductionmentioning
confidence: 99%